Analysis of the Implementation of Government Policy Through the Transcend Strategy of the Indonesian National Army in Efforts to Resolution the Papua Conflict: Analisis Implementasi Kebijakan Pemerintah Melalui Transcend Strategy Tentara Nasional Indonesia Dalam Upaya Resolusi Konflik Papua - Rasid Priesdiantoro; Yulian Azhari; Puguh Santoso; Pujo Widodo; Achmed Sukendro (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The conflict in Papua often stems from dissatisfaction over natural resource distribution, human rights issues, and calls for greater autonomy or even independence. The presence of armed groups and related violence adds complexity to the situation. This research aims to analyze the implementation of government policies through the Transcend Strategy of the Indonesian National Armed Forces in resolving the Papua conflict. It is a qualitative study with a descriptive design, drawing data from literature sources such as online media, journals, and relevant books. The findings indicate that the Indonesian National Armed Forces (TNI) play a crucial role as one of the key stakeholders in the region's conflict resolution efforts. International perspectives and government policies in responding to the Papua conflict are also considered. The Transcend method, emphasizing actors, culture, and structure, is utilized to analyze the implementation of government policies aimed at conflict resolution in Papua. The results underscore the necessity for policies such as adequate budget allocation to support special operations in Papua, the development of macro policies specific to Papua, engagement with and participation of Papua's communities, and policies regarding training and protection of human rights for TNI-Polri personnel involved in special operations in Papua. These policies aim to create stable, secure, and sustainable conditions in Papua, enhancing the well-being of local residents while safeguarding national sovereignty and security.